Genetic variants associated with response to lithium treatment in bipolar disorder: a genome-wide association study - Hou, Liping; Heilbronner, Urs; Degenhardt, Franziska; Adli, Mazda; Akiyama, Kazufumi; Akula, Nirmala; Ardau, Raffaella; Arias, Bárbara; Backlund, Lena; Banzato, Claudio E M; Benabarre, Antoni; Bengesser, Susanne; et al. (Lancet (London, England), 2016)
BACKGROUND: Lithium is a first-line treatment in bipolar disorder, but individual response is variable. Previous studies have suggested that lithium response is a heritable trait. However, no genetic markers of treatment response have been reproducibly identified. METHODS: Here, we report the results of a genome-wide association study of lithium response in 2563 patients collected by 22 participating sites from the International Consortium on Lithium Genetics (ConLiGen). Data from common single nucleotide polymorphisms (SNPs) were tested for association with categorical and continuous ratings of lithium response. Lithium response was measured using a well established scale (Alda scale). Genotyped SNPs were used to generate data at more than 6 million sites, using standard genomic imputation methods. Traits were regressed against genotype dosage. Results were combined across two batches by meta-analysis. FINDINGS: A single locus of four linked SNPs on chromosome 21 met genome-wide significance criteria for association with lithium response (rs79663003, p=1·37 × 10(-8); rs78015114, p=1·31 × 10(-8); rs74795342, p=3·31 × 10(-9); and rs75222709, p=3·50 × 10(-9)). In an independent, prospective study of 73 patients treated with lithium monotherapy for a period of up to 2 years, carriers of the response-associated alleles had a significantly lower rate of relapse than carriers of the alternate alleles (p=0·03268, hazard ratio 3·8, 95% CI 1·1-13·0). INTERPRETATION: The response-associated region contains two genes for long, non-coding RNAs (lncRNAs), AL157359.3 and AL157359.4. LncRNAs are increasingly appreciated as important regulators of gene expression, particularly in the CNS. Confirmed biomarkers of lithium response would constitute an important step forward in the clinical management of bipolar disorder. Further studies are needed to establish the biological context and potential clinical utility of these findings. FUNDING: Deutsche Forschungsgemeinschaft, National Institute of Mental Health Intramural Research Program.
Keywords: Bipolar Disorder; Lithium Compounds; Genotype; Female; Phenotype; bipolární porucha; Genome-Wide Association Study; výsledek terapie; ženské pohlaví; jednonukleotidový polymorfismus; receptory GDNF; lidé; Polymorphism, Single Nucleotide; genotyp; Treatment Outcome; Genetic Variation; sloučeniny lithia; Glial Cell Line-Derived Neurotrophic Factor Receptors; prospektivní studie; Male; Prospective Studies; celogenomová asociační studie; lidé středního věku; fenotyp; mužské pohlaví; genetická variace; Middle Aged; Humans